The Normativity of Ecological Restoration Reference Models: An Analysis of Carrifran Wildwood, Scotland, and Walden Woods, United States. Issue 2 (4th May 2019) - Prior, Jonathan; Smith, Laura
ABSTRACT: In this article, we explore how ecological restoration reference models are produced and what work they do within an ecological restoration project. By tracing the genesis of two restoration reference models - at Carrifran Wildwood, Scotland, and Walden Woods, United States - we suggest that reference models are more than simply scientific-technical guidelines for restoration activities, and that they can be usefully conceptualised as normative visions of desired future ecosystem states, due to the range of values they are based upon. As a result, we challenge the widespread notion that reference models represent arbitrarily chosen moments in time.